Influence of slaughter weight on growth and carcass characteristics of Alentejano pigs - Freitas A.B.; Neves J.; Charneca R.; Tirapicos Nunes J.; Martins J.M. (5. International Symposium on the Mediterranean Pig, 2007)
To study the effects of slaughter weight on growth and carcass characteristics of Alentejano pigs, thirty pigs were used. 20 kg LW animals were allocated in individual pens outdoors and fed a commercial diet (15% CP, 3100 Kcal DE) offered at 85% ad libitum. Pigs were sequentially slaughtered in groups (n=5) with an average BW of 40, 70, 80, 90, 100 and 110 kg. The growing period, feed intake, feed: gain and feed cost per Kg gain increased significantly (P<0.05) with the increase of slaughter weight, but commercial yield of carcass decreased (51.7% at 40 kg, 45-45.6% at 70-80 kg and 41.5-42.9 at 90-110 kg). Lean percentage of ham decreased slightly (53.8 to 43.1%) and fat increased strongly (15.9 to 32.1%) with the increase of slaughter weight. Results suggested that the most desirable slaughter weight would be between 90-100 kg.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)